Competências na era digital e indústria 4.0: o gestor de tecnologia nos bancos brasileiros - Silva, José Luiz Alves da (2020)
The Information and Communication Technology Manager (ICT) is part of the Digital Transformation processes that world society goes through. It is one of the links between the development of Disruptive Technologies (DTs) and the construction of solutions applied to any and every field of human activity. Nevertheless, the constant study of Technology Managers as an element to accompany this period of transformation has not been verified in our preliminary research, as part of systematic practices in the scientific environment. There is work around managers and executives in general and even about the technology professional in their daily lives. But specific studies on the Technology Manager and their challenges in the banking environment are not easily found, especially given the Fourth Industrial Revolution and Industry 4.0, which has shaken the foundations that underpin the social, business and personal environment in the current globalized world. Thus, this dissertation research has as its main object the Technology Manager in the major Brazilian banks, seeking to study their Competencies in the Digital Age and Industry 4.0, exploring the skills and abilities needed for this professional to work in the Next decade. For this, this work studies the scenarios of global transformation, the banking environment in our country and addresses four competency models used worldwide. It presents the results of the field research carried out, makes its analysis and, from there, proposes the possibility of a new skills profile, to be evaluated as an alternative for eventual application within the Next 10 years. The methodology applied so that the described purposes could be met was an exploratory approach, of a qualitative nature, with a data collection through interviews with a semi-structured script, applied to Executives and Senior Managers of the banking segment and technology area in Brazil